IMPLEMENTASI SISTEM SEWA MOBIL PRIBADI BERBASIS WEB UNTUK USAHA MIKRO KECIL MENENGAH (UMKM) - Iriawan, Arya Maulana Putra; Bororing, Grace Martha Geertruida (Jurnal Informatika dan Bisnis, 2023)
The development of information technology is increasing, and has begun to penetrate almost all areas of life, including the business field. The need for transportation facilities, especially cars, is increasing in support of community activities, especially in the Jakarta area and its surroundings. To facilitate people who do not own a car, car rental services can be a solution. Conventional car rental service methods are considered to be incompatible with current technological developments, because they still use manual data recording. The design of the car rental system is expected to help overcome the problems described above, both for renters and car owners, especially for Micro, Small and Medium Enterprises (MSMEs). This research was conducted using the agile method. The result of this research is a web-based car rental system application. From the research conducted, it can be concluded that with this car rental system, it is easier for users to carry out the administration of this car rental, thus affecting data collection for the better.